The colours of concrete as seen by X-rays and neutrons. (November 2019) - Roubin, Emmanuel; Andò, Edward; Roux, Stéphane
Abstract: Both x-ray tomography and neutron tomography give very detailed insight in the microstructure of concrete. However, their different contrasts, due to different compositional sensitivities, make one modality more relevant for some features. The present study shows that both types of images acquired on the same specimen may be registered onto each other, after the statistical joint distribution of absorption coefficients has been learned. A Gaussian mixture model has been used to identify up to five different phases having different signatures. A staggered algorithm consisting in i) adjusting the joint histogram to fit phases and their variances and ii) registering the two 3D images onto each other, within a multi-scale algorithm is presented in details. The analysed experimental data illustrates the benefit of using jointly both modalities as compared to their parallel usage.